SURGICAL TREATMENT OF PRIMARY CATECHOLAMINE HYPERTENSION - Путинцев, Александр Михайлович; Францев, Роман Сергеевич; Струкова, Оксана Анатольевна; Лишов, Евгений Владимирович; Каретников, Тимофей Анатольевич; Васильева, Эльвира Александровна (Medicine in Kuzbass, 2025)
Modern diagnostic methods have led to the fact that adrenal lesions with and without clinical manifestations (incidentalomas) have become increasingly common. The basis of adrenal lesions is also the development of venous hypertension of the left renal vein, caused by impaired outflow due to atypical variants of renal vein syntopy, the influence of arterial structures, and the absence of valves in the left adrenal vein. Numerous studies show a connection between arterial hypertension and the production of significant volumes of catecholamines and hormones of the adrenal cortex. Objective – was to study the results of surgical treatment of arterial hepertonia and to identify a group of patients with primary catecholamine hypertension. Materials and methods. In the Kemerovo Regional Hospital, in the department of vascular surgery, from 1985 to 2001, 233 patients with arterial hypertension of various origins were operated on. From this group of patients, we identified 56 patients where the clinic proceeded with sympathoadrenal crises, and morphological material revealed various pathology in the adrenal glands. Results. The analysis of the clinic, diagnosis, and morphology in 59 patients showed that there is a disease with its etiology, pathogenesis, and clinical manifestations. The clinical marker is sympathoadrenal crises. Morphology is structural changes in the left adrenal gland and extremely rarely in the right. Adrenalectomy leads to recovery or significant clinical improvement. Conclusion. We came to the conclusion about the existence of primary catecholamine arterial hypertension as an independent disease.